The structure of natively iodinated bovine thyroglobulin. Issue 11 (2nd November 2021) - Kim, Kookjoo; Kopylov, Mykhailo; Bobe, Daija; Kelley, Kotaro; Eng, Edward T.; Arvan, Peter; Clarke, Oliver B.
Abstract : Thyroglobulin is the precursor protein that serves as a substrate for thyroid hormone synthesis. Here, a three‐dimensional cryoEM reconstruction of bovine thyroglobulin at an overall resolution of 2.6 Å is presented. The structure facilitates the definitive identification of thyroxine (acceptor) and dehydroalanine (donor) sites at two of the most evolutionarily conserved sites of hormone formation in vertebrates. Abstract : Thyroglobulin is a homodimeric glycoprotein that is essential for the generation of thyroid hormones in vertebrates. Upon secretion into the lumen of follicles in the thyroid gland, tyrosine residues within the protein become iodinated to produce monoiodotyrosine (MIT) and diiodotyrosine (DIT). A subset of evolutionarily conserved pairs of DIT (and MIT) residues can then engage in oxidative coupling reactions that yield either thyroxine (T4 ; produced from coupling of a DIT `acceptor' with a DIT `donor') or triiodothyronine (T3 ; produced from coupling of a DIT acceptor with an MIT donor). Although multiple iodotyrosine residues have been identified as potential donors and acceptors, the specificity and structural context of the pairings ( i.e. which donor is paired with which acceptor) have remained unclear. Here, single‐particle cryogenic electron microscopy (cryoEM) was used to generate a high‐resolution reconstruction of bovine thyroglobulin (2.3 Å resolution in the core region and 2.6 Å overall), allowing the structural characterization of two post‐reaction acceptor–donor pairs as well as tyrosine residues modified as MIT and DIT. A substantial spatial separation between donor Tyr149 and acceptor Tyr24 was observed, suggesting that for thyroxine synthesis significant peptide motion is required for coupling at the evolutionarily conserved thyroglobulin amino‐terminus.